COMPARATIVE ANALYSIS OF A COMPOUND SENTENCE WITH CONNECTIVE RELATIONS IN THE RUSSIAN AND KARAKALPAK LANGUAGES - Masharipova Svetlana (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article presents a comparative and typological analysis of compound sentences with connective relations of the Russian and Karakalpak languages, revealing the phenomena of similarity and differences of these constructions in the contacting languages, allowing determining possible manifestations of interference in the Russian speech of Karakalpak students.